New autoinjector technology for the delivery of subcutaneous methotrexate in the treatment of rheumatoid arthritis. (September 2014) - Schiff, Michael; Jaffe, Jonathan; Freundlich, Bruce; Madsen, Patrick
<x xml:space="preserve">Abstract</x> Methotrexate (MTX) is the cornerstone of treatment for rheumatoid arthritis (RA), and is widely used both as first-line therapy and as an important component of long-term therapy. Although subcutaneous MTX is typically delivered orally, parenteral administration offers benefits with respect to tolerability and systemic exposure, and may be an underutilized treatment option. The RA patient population presents specific challenges for safe and accurate administration of parenteral therapies, because of common symptoms of joint pain and limited manual dexterity. These challenges may contribute to the low incidence of parenteral MTX administration. A novel MTX autoinjector (MTXAI) was recently introduced, which is designed to facilitate subcutaneous MTX self-administration among patients with RA. Here we review the development and utility of the MTXAI in the treatment of RA, and discuss how this technology may facilitate the use of subcutaneous MTX.